A solid-state [2 + 2] photodimerization involving coordination of Ag(I) ions to 2-pyridyl groups. Issue 16 (17th September 2018) - Campillo-Alvarado, Gonzalo; Aslan, Katerina; Sinnwell, Michael A.; Reinheimer, Eric W.; Santhana Mariappan, S. V.; MacGillivray, Leonard R.; Groeneman, Ryan H.
Abstract: Photoreactive Ag(I) complexes of p -toluenesulfonate ions with the unsymmetrical alkene trans -1-(4-acetoxyphenyl)-2-(2-pyridyl)ethylene1 is reported. The crystal [Ag( p -tol)(1 )2 ](H2 O) ( p -tol =  p -toluenesulfonate) undergoes a [2 + 2] photocycloaddition reaction in quantitative yield to afford the head-to-tail (ht) photoproduct rctt -1, 3-bis(2-pyridyl)-2, 4-bis(4-acetoxyphenyl)cyclobutane2 regioselectively. The aromatic rings of the olefin participate in face-to-face π–π interactions and adopt an anti-conformation to position the carbon–carbon double bonds (C = C) in a suitable orientation to undergo photoreaction between neighboring complexes. Graphical Abstract: